Optimization of insulin-like growth factor-1 supplementation enhances oocyte quality by modulating oxidative stress and apoptotic pathways during in vitro maturation of Kacang goat oocytes - Widjiati, Widjiati; Luqman, Epy Muhammad; Darsini, Ninik; Aulanni’am, Aulanni’am; Wan Jaafar, Wan Nor Fitri; Utama, Suzanita; Kurniawati, Devia Yoanita; Shabira, Zahra; Hendrawan, Viski Fitri (Veterinary World, 2025)
Background and Aim: Insulin-like growth factor-1 (IGF-1) plays a crucial role in folliculogenesis and oocyte maturation by regulating oxidative stress and apoptotic pathways. However, the optimal IGF-1 concentration for small ruminant oocytes, particularly the native Kacang goat, remains undefined. This study aimed to determine the optimal IGF-1 dose for improving oocyte quality during in vitro oocyte maturation (IVM) by evaluating oxidative stress and apoptosis markers. Materials and Methods: Ovaries (n = 120) were collected from local slaughterhouses, and cumulus–oocyte complexes were aspirated, selected, and randomly divided into four groups: Control (0 ng/mL IGF-1) and treatments with 50, 100, and 150 ng/mL IGF-1 supplementation. Mature oocytes were analyzed for oxidative stress biomarkers, including superoxide dismutase (SOD-1), glutathione (GSH), and malondialdehyde (MDA), using an enzyme-linked immunosorbent assay, and for apoptosis regulators, B-cell lymphoma 2-associated X protein (BAX), B-cell lymphoma-2 (BCL-2), and cytochrome c, using immunocytochemistry. Data were analyzed using one-way analysis of variance and Duncan’s post hoc test (p < 0.05). Results: IGF-1 supplementation produced concentration-dependent effects. The 100 ng/mL group (T2) exhibited the highest SOD-1 (2.07 ± 0.60) and GSH (8.07 ± 1.79) levels (p < 0.05), while MDA increased with higher IGF-1 doses, indicating a threshold beyond which oxidative stress is induced. Anti-apoptotic BCL-2 and cytochrome c expressions peaked at 50 ng/mL IGF-1 (10.73 ± 1.56 and 11.73 ± 0.99, respectively), whereas the pro-apoptotic marker BAX was lowest in the same group and increased at higher doses. The findings suggest that 50 ng/mL IGF-1 effectively maintains redox balance and mitochondrial stability through phosphatidylinositol 3-kinase/protein kinase B-mediated regulation. Conclusion: This study demonstrates, for the 1sttime, a dose-dependent, biphasic effect of IGF-1 on oxidative and apoptotic pathways in Kacang goat oocytes. An optimal concentration of 50 ng/mL IGF-1 enhances oocyte maturation by balancing antioxidant defense and anti-apoptotic mechanisms, whereas higher concentrations induce oxidative stress. These findings establish a breed-specific IVM optimization protocol that supports genetic preservation and sustainable reproductive biotechnology for indigenous goats.